The Diplomatic Mission of the Armenian Delegation in Berlin (April-June 1918) - Petrosyan, Nushik (YSU Journal of International Affairs, 2024)
The article highlights the diplomatic activities and strategic steps of the Armenian delegation in Berlin in the critical months in Armenian history in 1918 (April-June). After the end of the First World War and against the backdrop of the collapse of the Russian Empire, the Armenian delegation, in a difficult geopolitical situation, began its activities to ensure international recognition and support for the new independent Republic of Armenia. Based on the analysis of primary sources and diplomatic correspondence, the article reflects the efforts of the delegation during the period of research to strengthen Armenian statehood against the backdrop of continuing conflicting global interests, and also focuses on the delegation’s relations with the German authorities and the Ottoman Empire in the midst of war, tense international situation, assessing its impact on Armenia’s desire for independence and survival. The article sheds light on the challenges and opportunities faced by the Armenian delegates in Berlin at the most important stage in the history of the establishment of statehood.